Facile synthesis of NIR and Visible luminescent Sm3+ doped lutetium oxide nanoparticles. (February 2017) - Locardi, F.; Gianotti, E.; Nelli, I.; Caratto, V.; Martinelli, A.; Ferretti, M.; Costa, G.A.; Canesi, L.; Balbi, T.; Fasoli, M.; Martini, M.; Estevão, B.M.; et al.
Graphical abstract: Highlights: Samarium doped-lutetium oxide nanoparticles smaller than 15 nm were obtained by co-precipitation method. The Sm3+ loading was carefully evaluated in order to maximize Sm3+ emission avoiding concentration quenching phenomena. Intense Sm3+ NIR emission was observed. The nanoparticles showed no toxicity at low concentration towards to HECV cells. Abstract: A series of Sm 3+ doped Lu2 O3 nanoparticles have been synthesized via a simple co-precipitation method using oxalic acid as precipitant. The obtained compounds showed a platelet-like morphology with diameter ranging between 10 and 14 nm. The cell parameters increased with the increase of doping, due to the substitution of Lu 3+ with larger Sm 3+ ; also a progressive increase of the lattice strain has been induced. Sm 3+ doped Lu2 O3 nanoparticles showed interesting Vis and NIR emission, which was carefully evaluated together with lifetime measurements. In particular, the system with the lowest Sm 3+ loading exhibited the best photoluminescence performances. Preliminary cell viability test evidenced that Sm 3+ doped Lu2 O3 nanoparticles are not toxic, underlining their potential application a NIR luminescent probes in bioimaging.